Bürgerliche Freiheit Politische Philosophie von Hobbes bis Constant - Herb, Karlfriedrich (Praktische Philosophie, 1999)
This book asks about the concept of political freedom, its institutional expression and the possibilities of its historical mediation. The systematic reconstruction begins with Hobbes and ends with Constant. The presentation of the anatomy of the contractual oncept of freedom and its liberal criticism centers on the basic concepts of freedom - power - history.